Calculation of building structures and features of its automation technology - Shkurupiy, Oleksandr; Mytrofanov, Pavlo; Pashchenko, Andrii; Kozichko, Ivan (Academic journal Industrial Machine Building Civil Engineering, 2019)
Recently, the issues of evaluating the quality of building structures and predicting their reliability are becoming increasinglyimportant, especially for the construction of industrial facilities of the old fund. Powerful mathematical methods are beingdeveloped to evaluate the performance of structures and predict their reliability, but there are no automated computer systemsfor such analysis. At present, programs for the determined calculation of structures have been developed, which implementmethods for the resistance of materials, theoretical and construction mechanics, but they do not provide an opportunity to determineand predict reliability, especially objects of the old fund. The methods of the classical reliability theory combinedwith the methods of statistical modeling are used in the work, which requires the use of modern IT technologies methodswith the development of appropriate software systems
Keywords: construction; reliability; automated computer systems; software complex; stress-strain state